Flourishing in the holistic classroom - Tucker, Lisa Marie (Current perspectives in holistic education, 2021)
"In a time of unprecedented changes globally, Flourishing in the Holistic Classroom offers an alternative educational model to mechanistic learning; one that is dynamic and adaptive. The book offers key principles, dispositions, and practices that holistic educators draw from to create learning environments in which their students can flourish. This book describes learning that is based on a balance of inner and outer ways of knowing, with an emphasis on the inner life or soul of the learner. This is illustrated through accounts of running an arts camp using the inquiry process and experiences with teacher candidates. A key principle of holistic education is connection, which is explored through experiential examples such as connections between learners and each other, the teacher, and their subject of study. The role that mindfulness practice and teacher presence plays in the classroom, as well as working with fear and vulnerability are addressed through detailed narratives. The breadth of the author's experience including being an early years teacher, a director of programs and exhibits in a children's museum, and working with pre-service teachers is woven throughout the book. Reflections from former teacher candidates highlight the influence that holistic pedagogy has on learners. The book concludes with an invitation to the reader to embrace a holistic, integrative approach to education, which creates fertile ground for student flourishing. Flourishing in the Holistic Classroom is intended to support teachers, administrators, academics, pre-service teachers and graduate students"--